UTILITIES AND LIMITATIONS OF CURRENT ANIMAL MODELS OF DEPRESSION - Ramjattan, Andy; Pereira Lexley M, Pinto; Dhingra, Sameer (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Depression is one of the most debilitating medical conditions in the world today, yet its etiologies remain imprecise, and current treatments are not wholly helpful. Depression is more than just a feeling of sadness. Depression can affect the daily routine of an individual disrupting work, play, and overall ability to concentrate. People with depression usually experience a lack of interest and enjoyment in daily activities, notable weight loss or gain, sleeplessness or excessive sleeping, lack of energy, inability to concentrate, feelings of worthlessness or shame, and recurrent thoughts of suicide (diagnostic and statistical manual-V). It is projected to be the second leading cause of disability worldwide by 2020. It is estimated that depression currently affects 350 million people from around the world. There are a number of drugs of different pharmacological classes being used in the treatment of clinical depression. Animal models are indispensable tools in the search to identify new antidepressant drugs and to provide insights into the neuropathology that underlies the idiopathic disease state of depression. Animal models of depression can be used for a variety of purposes, including use as a tool for investigating aspects of the neurobiology and pathophysiology of depression, as an experimental model for studying the mechanism of action of antidepressant drugs and for screening antidepressant activity. None of existing animal models currently fulfil the existing criteria for an ideal animal model, and therefore, demands an insight view of the existing models of depression. This article attempts to review the most widely used animal models and highlights their important features with respect to different pharmacological classes of antidepressant drugs.